Robotic assisted urethral sparing simple prostatectomy: the way to solve LUTS due to large prostate and maintain ejaculation - Cristian Fiori (Urology Video Journal, 2022)
Objectives: To present our Urethral Sparing Robotic-Assisted Simple Prostatectomy (usRASP) technique for large Benign Prostatic Enlargement (BPE) and to evaluate its efficacy in maintaining antegrade ejaculation. Patients and surgical procedures: In this prospective study we enrolled consecutive patients who underwent RASP with urethral-sparing intent for large (>80cc) prostate at our Institution.Demographic variables were recorded. Functional data including uroflowmetry, PVR evaluation, IPSS score and MSHQ-EjD were assessed before the intervention and after 1, 3, 6 and 12 months post-operatively. Perioperative data were equally collected. Surgical technique: the procedure starts as a standard RASP, left and right lobes are enucleated separately leaving the urethra untouched. Prostatic capsule is then sutured by using a 3/0 barbed suture.On the basis of the final intraoperative result, patients were divided into three subgroups (full, partial or failed urethral sparing). Perioperative and functional results of these three subgroups were then compared. Results: 124 patients were enrolled, mean age was 67 y (± 6.5), mean prostate size was 140 cc (+_32cc), mean operative time was 110′ (97–122). No Clavien-Dindo >2 grade complications were recorded. Full and partial urethral-sparing RASP was performed in 81 and 25 cases respectively whilst in 18 cases (15%) the procedure was converted to standard RASP. Qmax increased of 16 ml/sec (+200%) and IPSS score decreased (from 20 to 5 points, -75%) from baseline (p<0.05). Overall, ejaculation was maintained in 76 of 93 pts (82%) who had normal ejaculation preoperatively, all patients undergone standard RASP lost ejaculation.Moreover, in partial or full urethral sparing group, catheterization time and post-operative stay was shorter, whilst no difference in terms of Qmax or IPSS score was noted between the groups.Small sample size and short follow-up time represent the major limits of this study. Conclusion: usRASP is feasible, safe and effective in solving benign prostatic obstruction due to large prostate and allows maintaining ejaculatory function in the vast majority of the patients.